Constraining barium isotope fractionation in the upper water column of the South China Sea. (1st November 2020) - Cao, Zhimian; Li, Yating; Rao, Xinting; Yu, Yang; Hathorne, Ed C.; Siebert, Christopher; Dai, Minhan; Frank, Martin
Abstract: Enabled by the success in the determination of stable barium (Ba) isotopic compositions in seawater, Ba isotopes have been suggested as a novel tool to study physical and biogeochemical processes in the present and past ocean. However, a better understanding of the fractionation of Ba isotopes during particle-seawater interactions is a prerequisite for such applications. In this study, we use an extensive data set of concentrations and isotopic compositions of dissolved Ba (DBa and δ 138 BaDBa ) and bulk particulate Ba (pBabulk and δ 138 BapBabulk ) collected in the northern South China Sea (NSCS) to constrain Ba isotope fractionation in the upper ocean. Seawater and suspended particle samples for Ba isotope measurements were collected in January 2010 along a transect from the outer shelf to the lower slope. The water column profiles reaching depths of 1000 m are characterized by a general decrease of δ 138 BaDBa and an increase of DBa with depth. However, δ 138 BaDBa signatures are essentially constant at +0.6‰ in the upper 150 m of the entire study area. The corresponding δ 138 BapBabulk, which primarily represents the isotopic compositions of oceanic or excess particulate Ba (pBaxs ), is consistently lower than δ 138 BaDBa but also constant at values of +0.1 to +0.2‰. This suggests that the same Ba isotope fractionation process prevails above 150 m on the NSCS outer shelf and slope resulting in a constant in situ fractionation factor of −0.5‰. This value is consistent with previously reported values of −0.4 to −0.5‰ in the upper 200 m of the open ocean and a lake. Moreover, we observe significant differences of pBaxs distributions from those of particulate calcium, particulate organic carbon and nitrogen, and biogenic silica indicating that passive adsorption onto particles rather than active biological utilization is most likely the primary process inducing Ba isotope fractionation in the upper NSCS. The constant δ 138 BapBabulk signatures suggest that particulate Ba isotopes integrate reliable information during transformation of DBa to pBaxs and are thus a more robust proxy for total particle fluxes than pBaxs concentrations, which show variable values potentially affected by other processes (e.g., particle sinking and/or zooplankton grazing) and thus reflects "snapshot" processes in the water column. We contend that biological productivity plays only a subordinate role in regulating the surface Ba isotopic composition of bulk suspended particles. The extent to which Ba isotopes may nevertheless be a reliable proxy for present and past export productivity requires further analyses of the δ 138 Ba signature of specific Ba carriers such as barite throughout the water column and in the sediments.